Performance and emission evaluation of a compression ignition engine using a biodiesel (apricot seed kernel oil methyl ester) and its blends with diesel fuel - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
In this study, apricot (Prunus armeniaca) seed kernel oil was transesterified with methanol using potassium hydroxide as catalyst to obtain apricot seed kernel oil methyl ester. Neat apricot seed kernel oil methyl ester and its blends with diesel fuel were tested in a compression ignition diesel engine to evaluate performance and emissions. Apricot seed kernel oil methyl ester and its blends can be successfully used in diesel engines without any modification. Lower concentration of apricot seed kernel oil methyl ester in blends gives a better improvement in the engine performance and exhaust emissions. Therefore lower percent of apricot seed kernel oil methyl ester can be used as additive. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Alternative fuels; Prunus armeniaca; Apricot seed kernel oil methyl ester; Biodiesel blend; Engine performance; Exhaust emissions; WASTE COOKING OIL; VEGETABLE-OIL; COMBUSTION CHARACTERISTICS; EXHAUST EMISSIONS; TURKISH ORIGIN; PALM OIL; TRANSESTERIFICATION